3D Parametric Modeling of Complex Geological Structures for Geotechnical Engineering of Dam Foundation Based on T‐Splines. (25th January 2018) - Zhang, Yichi; Zhong, Denghua; Wu, Binping; Guan, Tao; Yue, Pan; Wu, Han
Abstract: We propose a novel geological modeling method based on T‐splines for computer‐aided design (CAD) and building information modeling (BIM) systems of geotechnical engineering and perform original research on special T‐splines modeling strategies and the algorithm aiming at depicting structural complexity to develop and introduce the T‐splines technology into engineering geological modeling. A methodology of parametric geological modeling with T‐splines is established, where a topology‐geometry modeling strategy is adopted, the inhomogeneity, arbitrary connectivity and discontinuity of geological structures are quantified and associated with T‐spline surface elements in the topology phase. A representative parametric algorithm called IBALR is presented in the context of dam foundation geological modeling to generate an inhomogeneous local refined T‐mesh with high genus topology which can fit a complex geological layer. The proposed method is flexible and effective in improving geological representation within geotechnical engineering.